Harmonizing law and faith: The validity of female instrumentaire witnesses in notarial deeds and the principle of gender justice - Effendi, Basri; Qasthary, Auzan; Angkasa, Muhammad Akbar; Lestari, Chadijah Rizki (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
The issue of female instrumentary witnesses in notarial deeds is significant due to differing perspectives between Indonesian positive law and Islamic law. The Notary Office Act (UUJN) does not differentiate witnesses based on gender, as long as they are adults, legally competent, and independent. In contrast, some classical Islamic views consider women’s testimony in muamalah matters to be worth half that of men, as stated in Surah Al-Baqarah verse 282. This raises questions regarding the validity of notarial deeds involving female instrumentary witnesses. This study employs a normative juridical method with a conceptual approach through library research, including UUJN, the Qur’an, classical exegesis, and academic literature. The analysis is qualitative with deductive reasoning, comparing positive legal norms and Islamic law, while also interpreting their relevance through the principle of maqashid al-shari‘ah. The findings show that under Indonesian positive law, a notarial deed remains valid even with female witnesses, since the key requirement lies in legal competence rather than gender. Meanwhile, classical Islamic law restricts women’s testimony, but contemporary interpretations grounded in maqashid al-shari‘ah emphasize justice and equality, thereby granting women equal standing in giving testimony. In conclusion, the use of female instrumentary witnesses in notarial deeds does not contradict Indonesian positive law or contemporary Islamic legal principles. This study highlights the importance of harmonizing national law and Islamic law so that Indonesia’s legal system can be more responsive to justice and gender equality values.